Investigating the role of environmental taxes and regulations for renewable energy consumption: evidence from developed economies. Issue 1 (31st December 2022) - Bashir, Muhammad Farhan; MA, Benjiang; Bashir, Muhammad Adnan; Radulescu, Magdalena; Shahzad, Umer
Abstract: The current study aims to explore the role of environmental taxes and regulations for the renewable energy consumption, focusing on reporting policy suggestions to overcome climate change issues and achieve environmental sustainability. The main objective of this paper is to examine the relation between renewable energy, environmental taxes, environmental technologies, and environmental regulations in 29 OECD countries during 1996–2018. More precisely, we inspect the impact of the environmental regulations and environmental technologies on the renewable energy consumption. The authors employ CIPS and CADF unit root tests, panel Westerlund co-integration test, FMOLS, and Quantile regression methods for the econometric analysis. The econometric analysis suggests that the environmental regulations impede the renewable energy consumption in OECD economies. The study suggests that environmental policy initiatives should focus on implementing environmental strategies to inspire cohesiveness between environmental regulations and the development of environmental technologies in order to promote the renewables industry in the developed countries.